Contrasting magmatic structures between small plutons and batholiths emplaced at shallow crustal level (Sierras de Córdoba, Argentina). (November 2016) - Pinotti, Lucio P.; D'Eramo, Fernando J.; Weinberg, Roberto F.; Demartis, Manuel; Tubía, José María; Coniglio, Jorge E.; Radice, Stefania; Maffini, M. Natalia; Aragón, Eugenio
Abstract: Processes like injection, magma flow and differentiation and influence of the regional strain field are here described and contrasted to shed light on their role in the formation of small plutons and large batholiths their magmatic structures. The final geometric and compositional arrangement of magma bodies are a complex record of their construction and internal flow history. Magma injection, flow and differentiation, as well as regional stresses, all control the internal nature of magma bodies. Large magma bodies emplaced at shallow crustal levels result from the intrusion of multiple magma batches that interact in a variety of ways, depending on internal and external dynamics, and where the early magmatic, growth-related structures are commonly overprinted by subsequent history. In contrast, small plutons emplaced in the brittle-ductile transition more likely preserve growth-related structures, having a relatively simple cooling history and limited internal magma flow. Outcrop-scale magmatic structures in both cases record a rich set of complementary information that can help elucidate their evolution. Large and small granitic bodies of the Sierra Pampeanas preserve excellent exposures of magmatic structures that formed as magmas stepped through different rheological states during pluton growth and solidification. These structures reveal not only the flow pattern inside magma chambers, but also the rheological evolution of magmas in response to temperature evolution. Highlights: The thermal maturation of a pluton and its growth conditions influence the nature and preservation of magmatic structures. Small plutons have a relatively simple cooling history and more likely preserve growth-related structures. Batholiths emplaced at shallow crustal levels have a complex thermal and flow history. Deformation has a significant role in the segregation of residual melts in both syntectonic and post-tectonic granites. We discuss the influence of the growing history of the plutons in the development of their magmatic structures.